2013
DOI: 10.1016/j.ijscr.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Anterior sagittal approach without splitting the rectal wall

Abstract: The anterior sagittal approach without splitting the rectum is a feasible procedure which provides excellent exposure to the posterior urethra in most cases and leads to less morbidity as it avoids the splitting and suturing of the rectum anterior wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A technique proposed by Dómini et al and Benedetto et al in 1997 involved sectioning only the anterior rectal wall in an anterior sagittal transanorectal approach (ASTRA) to treat a urogenital sinus in adrenogenital syndrome [21] , [22] . Since its description, this technique has alternatively been performed without the splitting of the rectum and good results have been reported in current literature [23] . ASTRA provides excellent exposure of the posterior urethra and retrovesicular region, and allows the surgeon to perform dissection under direct vision.…”
Section: Discussionmentioning
confidence: 99%
“…A technique proposed by Dómini et al and Benedetto et al in 1997 involved sectioning only the anterior rectal wall in an anterior sagittal transanorectal approach (ASTRA) to treat a urogenital sinus in adrenogenital syndrome [21] , [22] . Since its description, this technique has alternatively been performed without the splitting of the rectum and good results have been reported in current literature [23] . ASTRA provides excellent exposure of the posterior urethra and retrovesicular region, and allows the surgeon to perform dissection under direct vision.…”
Section: Discussionmentioning
confidence: 99%
“…4 We applied the benefits of both the ASTRA and TUM techniques without splitting the rectal wall. 16 We placed the patient in a prone position with bowel preparation and antibiotic therapy. It provided excellent exposure without compromising the fecal continence mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It provided much better exposure however the morbidity associated with this technique could be potentially decreased if the anterior sagittal access were to be made without sectioning the rectum. Leite et al reported on their initial experience using anterior approach without rectal sectioning and concluded that the technique was feasible and provided excellent exposure to the posterior urethra in most cases [9]. The technique was less morbid as it avoided the splitting and suturing of the anterior rectal wall.…”
Section: Discussionmentioning
confidence: 99%